Biochemical and Sensory Characteristics of Dairy-Tigernut Yoghurt using Ginger as Bio-Preservative (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Tiger-nut milk is a good substitute for cow milk in yoghurt production because of its health benefit, accessibility and availability especially for people living in low-income countries, people living with lactose intolerance and vegetarian. Ginger extract (4%) was added as a bio preservative to improve the keeping quality of products obtained. Effect of ginger extract was studied on both tiger-nut yoghurt, cowmilk yoghurt and the blends. Microorganisms were identified during storage, total sugar and titratable acidity were evaluated and organoleptic properties were assessed. Microbial count was lower in samples with ginger extract and pathogenic microorganisms were not detected during storage. Microorganisms isolated were Lactobacillus delbrueckii, Streptococcus thermophilus, Lactobacillus plantarum, Pediococcus acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, acidilactic, Saccharomyces cerevisiae, Leuconostoc mesenteroides, Bacillus subtilis, Staphylococcus epidermidis, Aspergillus niger and Micrococcus roseus. Tiger-nut generally increased the total sugar and pH of the samples and reduced the titratable acidity. These findings suggested that addition of ginger can increase the keeping quality of dairy, tiger-nut yoghurt and their blends without altering the organoleptic properties thereby providing healthy diet and reducing nutritional related disease.
Keywords: Ginger; Plant milk; Sensory; Tiger-nut; Yoghurt